Le' Laundry / Nor Azilawaty M Ikhsan … [et.al.]. - M Ikhsan, Nor Azilawaty; Marali, Jurainah; Abdullah, Mohd Syafiq Akmal; Yussop, Norhazerah; Laing, Jeffery; Ali, Hazuwan (2014)
Our business name is Le' Laundry. This business formed based on the partnership ventures of six people whom also act as managers in the business.Basically, our core business is to provide a laundry service especially for the UiTM students and staffs in the new SAMARAHAN 2 campus. Aside from just providing regular services, we are also providing a pick up and drop service whereby we will collect clothes to be wash from them and deliver it back. As for our business here, basically Le' Laundry means "The Laundry”. We picked a French article which is the Le' to make it a little bit different even if it is just a simple name because less is more. Based on our motto “High Piles, No More!" we aim to give a hand to especially the students in the new campus in doing their laundry. As we can see, the hostel does not provide a very conducive place to dry off the clothes after washing and even the drying lines are not enough for the members in the house. They need to take turn and this is as well make the dirty clothes piled up. Our business provides assurance that the clothes send by students or staffs will be returned to them in original conditions, except it is cleaned.